THE PALEOENVIRONMENT AND THE EVOLUTION OF BRINES IN THE JORDAN-DEAD SEA TRANSFORM AND IN ADJOINING AREAS - Rosenthal E.; Flexer A.; Möller P. (My University, 2006)
One of the most important processes leading to the deterioration of groundwater in Israel is the migration of brines penetrating into fresh groundwater bodies. Such manifestations occur at an ever increasing frequency and in unexpected locations. The hydrochemistry of these processes reveals the possibility of involvement of several types of brines. The distribution and the hydrostratigraphic sequence of the brines is correlated with the evolution of paleoenvironments during the geological history of the region. Several major phases of brine and evaporite formation are discerned: The earliest phase occurred in the Paleozoic–Early Mesozoic (Yam Suf–Ramon–Lower Arad Groups) during which brines were generated by dissolution of evaporites. The second major phase in the evolution of brines occurred during the Mio-Pliocene. In the western areas of the country, the brines were generated mainly by the post-Messinian ingression of seawater which dissolved evaporites and reacted with the invaded rock sequence. In the Rift and in adjoining areas, the dominant brine was the final product of the evaporation of an inland marine lagoon (the Sdom Sea) which penetrated into an environment prevalently built of previously formed rocks and, particularly of clastic beds filling at that time, the nascent rift. From this evaporating lagoon precipitated evaporates, the dissolution of which produced brines. A further step in the hydrochemical evolution in the Rift was the creation of the Lisan Lake, which became progressively saline, probably as the result of dissolution and flushing of salts derived from the previous hypersaline Sdom Sea. The contemporary phase in the Rift is characterized by an ongoing process of flushing-out of residual brines and dissolution of evaporites by currently recharged fresh water. Throughout the geological history of the area, four major periods of flushing stand out. These occurred between the Triassic and the Jurassic, at the end of the Jurassic, as the result of the Oligocene uplift and as part of the Messinian event. As the result of these processes, the rock-sequences were flushed off previously formed brines and evaporites and were “made ready” for following generations of liquids.
Keywords: STRUCTURAL EVOLUTION; PALEOGEOGRAPHY; PALEOHYDROGEOLOGY; JORDAN-DEAD SEA-RED SEA RIFT; BRINES; Jurassic; Triassic; Pliocene; Oligocene; Messinian; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский